Denarrazione della storia, ripetizione del trauma, e alcuni tentativi di processare una traduzione “perduta” - Morresi, Renata (L'ospite ingrato, 2025)
This paper explores the reflections generated by the translation of Zong!, as told to the author by Setaey Adamu Boateng (2008) by nourbeSe philip, reflections which first took shape while I was translating the long poem and continued after the accusation towards the Italian version (Benway Series, 2021). As one of the translators, I interpreted Zong! as a reinvention of the archive of modernity, which becomes active memory in moments of crisis. I compare my interpretation with my re-reading of it as urged by philip, and I conduct the comparison also in the form of self-critique and reflection on an all-encompassing translatorial action. I will examine the limits and implications of the “lost” translation, taking into account the circumstances of the book’s production and its controversial reception, in the hope of fostering new avenues of practice and research.